Handbook of mangroves in the Philippines-Panay - Primavera, Jurgenne Honculada (Southeast Asian Fisheries Development Center Aquaculture Department, 2004)
The handbook includes key information on more than 30 species of mangroves in Panay Island and surrounding areas. It is designed for non-specialist readers for school, local government officials, NGOs and the public. For laypersons and researchers for identifying species in the field based mainly on appearance and habitat.